Associations of cortisol/testosterone and cortisol/sex hormone-binding globulin ratios with atherosclerosis in middle-age women. (May 2016) - Lee, Ju-Mi; Colangelo, Laura A.; Schwartz, Joseph E.; Yano, Yuichiro; Siscovick, David S.; Seeman, Teresa; Schreiner, Pamela J.; Liu, Kiang J.; Lloyd-Jones, Donald M.; Greenland, Philip
Abstract: Background and aims: The cortisol/testosterone (C/T) ratio has been hypothesized to be a better predictor of atherosclerosis than cortisol alone. No study has assessed whether the C/T and C/sex hormone-binding globulin (SHBG) ratios are associated with atherosclerosis in a U.S. population sample. Methods: This substudy included 367 women who had both cortisol from year 15 and testosterone and SHBG at year 16 of the Coronary Artery Risk Development in Young Adults study, an ongoing observational cohort in the United States. Of these, intima-media thickness (IMT) was available at follow-up year 20 in 339 (n = 332 with measurement at carotid bulb), and 303 were free of prevalent coronary artery calcium (CAC) at year 15. Area under the curve (AUC) of salivary cortisol was available in 302 individuals. Ratios of AUCs of cortisol to total testosterone, free testosterone, and SHBG were categorized into tertiles. Associations with CAC and IMT were assessed by regression models adjusted for age, race, body mass index, systolic blood pressure, menopause, oral contraceptive use, diabetes, alcohol, and smoking. Results: Only the highest tertile of the AUC/free testosterone ratio was positively associated with carotid bulb IMT (β = 0.088, P = 0.006). This tertile was also positively associated with new onset CAC between year 15 and 25 (OR 3.45, 95% CI 1.18–10.06). Tertiles of cortisol or testosterone alone were not associated with new onset CAC. Conclusion: AUC/Free testosterone ratio may be more associated with atherosclerosis in women than either indicator alone. The ratio may serve as a suitable biomarker of cortisol-linked stress. Highlights: AUC/free testosterone (FT) was associated with incident CAC and maximum CB. AUC/FT may be more associated with atherosclerosis than either indicator alone. The ratio may serve as a suitable biomarker of cortisol-linked stress.